Machine tool practices - Kibbe, Richard R.; Neely, John E; Meyer, Roland O; White, Warren T (Englewood Cliffs, N.J. : Prentice Hall, 1995)
The major objective of this book is to provide a current and richly illustrated text for those students training to become machine operators, machinists, or tool and die makers, either through apprenticeship training, or community college and vocational programs.
Includes index.
Keywords: Machine-tools.; Machine-shop practice